L’Analyse du Discours en Afrique francophone subsaharienne. Jalons et prospectives - Aimee-Danielle LEZOU KOFFI (Altralang Journal, 2021)
ABSTRACT: The aim of this article is to present the integration and trajectory of discourse analysis in Africa. First, we recall its close links with the French school of discourse analysis based on the mobility of scholarship holders from universities in sub-Saharan French-speaking Africa. The projects, initially individual, have provoked a theoretical scattering of research, the epistemological roots of which are then shown. Finally, we discuss the challenges of discourse analysis with the advent of the African Discourse Analysis Network (R2AD). This turning point in the development of the discipline in Africa seems to be part of a desire to disseminate research and for epistemological innovation.